Sodium fluoride impairs splenic innate immunity via inactivation of TLR2/MyD88 signaling pathway in mice. (December 2019) - Kuang, Ping; Guo, Hongrui; Deng, Huidan; Cui, Hengmin; Fang, Jing; Zuo, Zhicai; Deng, Junliang; Li, Yinglun; Wang, Xun; Zhao, Ling
Abstract: Fluoride is known to affect the inflammatory process and autoregulation of immune responses, but the molecular mechanism by which fluoride causes innate immune injury remain largely unknown. Also, studies on sodium fluoride (NaF)-caused alteration of TLR signaling are still lacking. In the present study, we examined the effects of NaF on the mRNA and protein expression levels of TLR2/MyD88 signaling pathway molecules in the mouse spleen by using the methods of qRT-PCR and Western blotting. Consequently, we elucidated the mechanism underlying the effects of NaF on innate immunity. Two hundred and forty ICR mice were randomly divided into 4 groups with intragastric administration of distilled water in the control group and 12, 24, 48 mg/kg of NaF treatment in the experiment groups for 42 days. The findings revealed that NaF impaired splenic innate immunity in mice via inactivation of TLR2/MyD88 signaling pathway. NaF-inactivated TLR2/MyD88 signaling pathway was identified by prominently downregulated mRNA and protein expression levels of TLR2/MyD88, IRAK4, IRAK1, TRAF6, TAK1, MKK4/MKK7 and c-Jun, which ultimately altered the expression levels of IL-1β, IL-4, IL-6 and IL-8 to attenuate innate immunity. Highlights: NaF exposure can impair splenic innate immunity. NaF inactivated the TLR2/MyD88 signaling pathway. NaF induced a causal cascade response to impact immune cytokines production.